RESPONSIBILITY ACCOUNTING FROM THE ONGOING EVALUATION OF ICT IN COMPANIES WITH ONLINE ACCOUNTING - Pastor Carrasco, Carlos Alberto (2011)
Technological advances (eg, electronic commerce and the Internet) have changed business practices and the process of recording and storing business transactions. Extensible Business Reporting Language (XBRL) will soon be incorporated into the accounting software and reporting that allow on-line real-time preparation, publication, examination, and extraction of financial information. Therefore, external auditors, independent evaluation should be used continuously, when most financial information exists in organizations is only in electronic form in the accounting systems and in real time. Continuous Assessment and its implications for independent auditors, are included in this document. They are also described and analyzed internal control considerations and audit procedures, Future audits will be common as is paperless audit clients increasingly shift to paperless systems. The developed audit software allows auditors to complete most procedures on-line. For online systems audit, auditors will need to incorporate an online software audit as a primary audit tool and gather evidence electronically. Should assess the impact of technology on the audit process, and discusses the future implications of technological trends for the auditing profession. More specifically, it provides an overview of how information technology has impacted audit planning, testing and documentation.